Razor Clams (Solen spp.) of Kuching Bay, Sarawak, Malaysia - Ruhana, Hassan; Siti Akmar Khadijah, Ab Rahim; Lee, Nyanti (Universiti Malaysia Sarawak, 2013)
Razor clam (Solen spp.) is one of the most important Bivalvia in Kuching Bay, Sarawak. They are filter feeders, infaunal marine bivalves that can be found in beaches comprising mixture of sand and mud. There are three species which co-exist in this area, with Solen regularis as the most common species. Local people harvest razor clams during late August to early March annually, either for source of income or domestic use. Preliminary survey recorded complaints from local people about decrease in harvest, therefore research was carried out to validate the matter. Transect line was used to assess density of razor clams and data collected in Asajaya showed that density of razor clams is decreasing (approximately 6,768 individuals/ ha in 2005; 4,868 individuals/ ha in 2006). Further research is designed to determine the spawning season; and qualitative data was obtained by interviewing local people regarding socio-economic aspects. The presence of gonad was recorded between August to late October and early development of gonad is most likely to begin in late January. Socio-economic data suggested that local people inherit rich local knowledge about razor clam distribution and high skill related to ecological-friendly methods used for harvesting but they have limited knowledge on science and conservation. Recently, a team of researchers from Universiti Malaysia Sarawak (UNIMAS) started a comprehensive project which aims to explore the possibility of establishing aquaculture or 'sea ranching' of razor clam in this area, hoping to reduce pressure on razor clam natural stock. This paper is about conservation efforts on razor clams of Kuching Bay, prospects and challenges.